To solve this problem you must apply the proccedure shown below:
1. You have the following expression given in the problem above:
![(1)/((x+2))+(1)/(5)=(6)/((x+5))](https://img.qammunity.org/2019/formulas/mathematics/high-school/o4bq5r7xas6gvbzek73xlmaac2coug1mwo.png)
2. You need to find the least common denominator on the rigth member of the equation and then, you must sum both fractions:
![((2)(5)+(x+2))/(5(x+2)) =(6)/((x+5))\\((x+12))/((5x+10))=(6)/((x+5))](https://img.qammunity.org/2019/formulas/mathematics/high-school/h5qdhdnbbkiqy2vccqel3cgb4c8hjfp1ga.png)
3. Now, solve for
, as following:
![(x+12)(x+5)=6(5x+10)\\ x^(2) -13x=0](https://img.qammunity.org/2019/formulas/mathematics/high-school/kfykmjwrp8781461oc3kq8puovmlzkxhf0.png)
4. Factor out the
:
![x(x-13)=0\\ x=0; x=13](https://img.qammunity.org/2019/formulas/mathematics/high-school/ffzhu4f2y3iqurdf76laqbrbgkajb6dhxj.png)
The answer is:
![x=0\\ x=13](https://img.qammunity.org/2019/formulas/mathematics/high-school/a0akto661w7vvumbjd7l0cf6w11e2r2fy4.png)